Tropical fruit tree species and climate change - Sthapit, B.R.; Ramanatha Rao, V.; Sthapit, S.R.; Bioversity International (2012)
Tropical fruits – full of rich nutrients and health properties – are adapted to hot and humid environments. Many tropical fruit species might spread beyond their current geographical limit whereas some species might exhibit irregular bearing of fruit. In this context, there are some important questions that need answers: What are the key characteristics that allow farmers to choose a new crop that they are not used to growing? Are farmers already experiencing impacts of climate change? If so, what are their adaptation strategies? Are there new opportunities for capitalizing tropical fruit tree genetic resources that benefit human kind? The study provides a state of knowledge to overcome threats to agriculture and food security, exploring new ways of helping vulnerable rural communities adjust to global changes in climate.